Making way for making : exploring faculty's conceptions of the maker movement in higher learning institutions - Nur Hidayah Sazali (Kulliyyah of Education, International Islamic University Malaysia, 2020)
This case study explores a faculty's conceptions of the maker movement, specifically referring to the faculty's perceived understanding, planning and expectations towards maker movement with respect to for the social sciences discipline (i.e., their perceived understanding of, planning and expectations towards it). The conceptual framework developed for this study looks into the interactions between people, means and activities in order to extract the best outcome of the maker movement; based on the four sets of learning and innovation skills (4Cs) namely: creativity, critical thinking, communication and collaboration. A qualitative case study approach was selected adopted for this study and a total of five 5 faculty members were interviewed, drawn from a purposive sampling. A semi-structured interview protocol was developed for the interview sessions. The study discovered that executing effective maker movement requires an extensive planning due to the abstract nature of the social science discipline. An interactive and engaging teaching and learning approach to develop the 4Cs should involve innovative maker identities, the right maker mindset together with appropriate environment and tools. The findings of the study could become an important framework towards future implementation of the maker movement within social sciences and encourage instructors to act as a catalyst to connect the right means and activities towards the learners' act of making. The study concluded that the maker movement is applicable to the social science discipline and should be expanded to make teaching and learning more effective and engaging.